The influence of pre-treatment on germination of three species of Catasetum (Orchidaceae) - Moraes, Milena Cristina; Bertão, Monica Rosa [UNESP]; Custódio, Ceci Castilho; Machado-Neto, Nelson Barbosa (FapUNIFESP (SciELO), 2023)
Asymbiotic germination techniques are successful in species of the Catasetum genus. The diverse composition of the culture media can be critical; however, viable seeds are required for asymbiotic germination. The reliable method for viability assessment is the tetrazolium test. A decisive step in the efficiency of the tetrazolium test is the seeds preconditioning with sucrose solution, which has the potential to improve germination. Therefore, this work aimed to evaluate the seed germination of three species of the genus Catasetum in culture media, preconditioned or not with sucrose solution. Seeds of the species Catasetum osculatum, Ctsm. galeritum and Ctsm. complanatum were assessed by tetrazolium test and germinated in two different media, pretreated or not with 10% sucrose solution. The statistical analysis showed that the use of sucrose pretreatment significantly increased the germination rates of the species. We conclude that the pretreatment with 10% sucrose for 24 hours, regardless of the species and the culture medium, significantly increases the germination of Ctsm. complanatum, Ctsm. galeritum and Ctsm. osculatum seeds.
Keywords: orchid; plant culture; seeds; sucrose solution; tetrazolium